Calcium Route in the Plant and Blossom-End Rot Incidence - Md. Yamin Kabir; Juan Carlos Díaz-Pérez (Horticulturae)
Calcium (Ca2+) is a macronutrient essential for the growth, development, yield, and quality of vegetables and fruits. It performs structural, enzymatic, and signaling functions in plants. This review examines Ca2+ translocation from soil to the fruit via the plant xylem network, emphasizing the importance of Ca2+ compartmentalization within fruit cell organelles in the development of calcium deficiency disorders such as blossom-end rot (BER). The underlying causes of BER and potential control measures are also discussed. Soil-available Ca2+, transported by water flow, enters the root apoplast through membrane channels and moves toward the xylem via apoplastic or symplastic routes. The transpiration force and the growth of organs determine the movement of Ca2+-containing xylem sap to aerial plant parts, including fruits. At the fruit level, the final step of Ca2+ regulation is intracellular partitioning among organelles and cellular compartments. This distribution ultimately determines the fruit’s susceptibility to Ca2+-deficiency disorders such as BER. Excessive sequestration of Ca2+ into organelles such as vacuoles may deplete cytosolic and apoplastic Ca2+ pools, compromising membrane integrity and leading to BER, even when overall Ca2+ levels are adequate at the blossom end. Effective BER management requires cultural and physiological practices that promote Ca2+ uptake, translocation to the fruit, and appropriate intracellular distribution. Additionally, the use of BER-resistant and Ca2+-efficient cultivars can help mitigate this disorder. Therefore, a comprehensive understanding of Ca2+ dynamics in plants is critical for managing BER, minimizing production loss and environmental impacts, and maximizing overall crop productivity.